Tabarruk dalam Perspektif Agama Islam - Fathimah Naufel Baradja; Sudarmadi Putra (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Tabarruk is a practice that hopes for blessings from Allah Ta'ala. Tabarruk itself is divided into 2, namely; Tabarruk is permitted and Tabarruk is prohibited. Tabarruk which is prohibited can plunge the perpetrator into the abyss of shirk. Indeed, only Allah is the best place to hope for blessings in life.